Comparative Assessment of the Proximate Composition, Functional Properties and Amino Acid Profile of Dioscorea bulbifera, Dioscorea alata and Dioscorea rotundata Found in Minna, Niger State - Eneogwe Okechukwu Godfrey; Obuye Faith; Ibrahim Izihyi Esther (Biology, Medicine, & Natural Product Chemistry, 2023)
The proximate composition, functional properties and amino acid profile of samples of Dioscorea alata, Dioscorea rotundata and Dioscorea bulbifera were investigated using standard analytical methods. The results showed that Dioscorea alata had the highest ash (5.590.06 %) and crude fiber content (12.120.20 %), indicating that it has more mineral stuffing and is best to reduce the risk of obesity. Dioscorea rotundata had the highest fat content (11.630.04 %) as well as the lowest moisture content (7.040.06 %), indicating that it is a better source of calories and has a longer shelf-life than other yam species analysed. Dioscorea bulbifera also had the highest crude protein (8.640.03 %) and carbohydrates (77.510.08 %) than other yam species analysed, indicating high bodybuilding capacity and a better source of energy than other yam samples analysed. Dioscorea alata showed the highest bulk density (0.870.02 g/cm3) and swelling capacity (15.250.03 g/g). It is indicating its usefulness in the reduction of paste thickness and water-holding capacity of starch granules respectively while Dioscorea rotundata, showed the highest water absorption capacity (164.020.02 %), oil absorption capacity (149.760.02 %) and dispersibility (72.170.01 %). This indicates its importance in the consistency and bulking of products, flavour retaining in food and reconstitution of flour samples in water to give a fine consistent paste during mixing. The yam species were also rich in amino acids which are building blocks of protein. However, Dioscorea rotundata was the richest in amino acid content, as it had 36.320.16 g/100g and 36.490.16 g/100g, for essential and non-essential amino acids respectively.